Ministry of Finance Decree No. 309 of the Year 2023 Amending Certain Provisions of the Executive Regulations of the Uniform Tax Procedure Law Promulgated by Minister of Finance Decree No. 286 of the Year 2021 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic